Metodologia para o monitoramento de sistemas de controle na indústria química - Souza, Davi Leonardo de (2011)
Control systems monitoring relates to ability to supervise the industrial plants operation, evaluating the controller performance by oscillation detection, disturbances, faults in sensors, valve stiction and diagnosing possible causes of problems that may degrade the productive capacity, managing alarms and providing possible strategies to act or even improve the eciency of operation. Control Process Monitoring (CPM) and Control Process Assessment (CPA) technologies are essential for maintaining the ecient during operation of industrial processes. This work presents a systematic method for monitoring of control systems in chemical industry, using a performance manager. This way it was investigated control systems using the performance index concept to quantify the degradation of controller's eciency, that is a tool to evaluate the behavior in industrial operation context. Performance index supplies the idea of as the control system is distant of best control idealized with same structure. Due the characteristics of reference behavior, that does not depend on the structure of control used, it can be evaluated controllers of several types and under several situations. This index was obtained by design of reference, using the factorization with interactor matrix generalized. Discover abnormalities in control systems is very important and complicated. In addition, was evaluated procedures subject to presence of oscillations, using an extension of the Karhunem-Loeve method and periodogramas. It was also evaluated, processes with valves stiction using the Yamashita method and faults in sensors and systems subjected to disturbances, using the principal components analysis (PCA) with T2 and Q statistics, with objective of detecting, isolating and diagnosing possible cause of control systems deterioration.